(3efgLjI GdHMK GdYdej (B: s (3ehLgI dWdHI GdSfI GdChdi (B(LMD) (3LPY eTJQc (B/ s - (3RhGhj, RcjIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2022)
(3eONd dYde GdefgLjI (B((3JYQja GdefgLjI , GdeOGQS GdefgLjI (B) (3, GdHMK GdYdej (B((3Gdeaghe , GdCfhGY , GdNUGFU (B) (3, efGgL GdHMK GdYdej , COhGJ LeY GdeYdheGJ GdGhdjI , GdeUGOQ h GdeQGLY h cjajI GdGaGOI efgG (B. s
(3GdeQGLY U(B.98s
Keywords: (3WQb GdHMKs